Evaluation of temperature rise following the application of diode and ErCr:Ysgg lasers: an ex vivo study - Adnan Öztürk; Burak Kocabalkan; Öznur Özalp; Mükerrem Hati̇poğlu; Olgu Nur Dereci̇; Alper Si̇ndel (Istanbul University, 2018)
DOI: 10.26650/eor.2018.479Purpose Erbium, chromium: yttrium, scandium, gallium, garnet (ErCr:Ysgg) lasers have been frequently used in oral surgical procedures and are almost seen as alternatives to diode lasers. The aim of this comparative study was to analyze in an animal model the thermal elevation induced by ErCr:Ysgg and diode lasers in soft tissue and bone. Materials and methods Thirty freshly dissected sheep mandibles containing bone and soft tissue were divided into 120 equal parts. Gallium-aluminum-arsenide (Ga-Al-As) diode laser (λ=940 nm) with 1, 2 and 5 W output powers and ErCr:Ysgg laser (λ=2780 nm) with 2.75, 4.5 and 6 W output powers were used on soft and bone tissues separately for 3 seconds with point application. Mean temperature values before and after application of the lasers were compared in soft tissue and bone. Results The minimum mean temperature value was observed with 2.75 W ErCr:Ysgg laser while irradiation with 5 W diode laser created the maximum values (p<0.05). Conclusion ErCr:Ysgg laser (λ=2780 nm) with 2.75 W power generates low levels of heat compared to diode lasers and may provide safer surgery in soft and bone tissues without destructive effects of temperature increase.